2011
DOI: 10.1242/jcs.081596
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary reconstruction of the retromer complex and its function in Trypanosoma brucei

Abstract: SummaryIntracellular trafficking and protein sorting are mediated by various protein complexes, with the retromer complex being primarily involved in retrograde traffic from the endosome or lysosome to the Golgi complex. Here, comparative genomics, cell biology and phylogenetics were used to probe the early evolution of retromer and its function. Retromer subunits Vps26, Vps29 and Vps35 are near universal, and, by inference, the complex was an ancient feature of eukaryotic cells. Surprisingly, we found DSCR3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
153
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(160 citation statements)
references
References 90 publications
6
153
1
Order By: Relevance
“…Disruption of sphingolipid biosynthesis through inhibition of serine palmitoyltransferase has a similar effect on the Golgi complex, but the effect is relatively mild (Fridberg et al, 2008). However, disruption of Golgi morphology upon depletion of T. brucei Rab28 parallels Vps26 knockdown in mammalian cells and trypanosomes (Seaman, 2004;Koumandou et al, 2011). The absence of conventional retromer cargo from trypanosomes means that direct investigation of retromer function is difficult, but the complex probably mediates similar functions in both systems (Koumandou et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Disruption of sphingolipid biosynthesis through inhibition of serine palmitoyltransferase has a similar effect on the Golgi complex, but the effect is relatively mild (Fridberg et al, 2008). However, disruption of Golgi morphology upon depletion of T. brucei Rab28 parallels Vps26 knockdown in mammalian cells and trypanosomes (Seaman, 2004;Koumandou et al, 2011). The absence of conventional retromer cargo from trypanosomes means that direct investigation of retromer function is difficult, but the complex probably mediates similar functions in both systems (Koumandou et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, disruption of Golgi morphology upon depletion of T. brucei Rab28 parallels Vps26 knockdown in mammalian cells and trypanosomes (Seaman, 2004;Koumandou et al, 2011). The absence of conventional retromer cargo from trypanosomes means that direct investigation of retromer function is difficult, but the complex probably mediates similar functions in both systems (Koumandou et al, 2011). Gross morphological aberrations at the Golgi complex potentially result through depletion of SNAREs or other factors required for correct homotypic fusion due to defective retrieval from late endosomes, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of the conservation of RME-8 (Koumandou et al, 2013) concluded that it is well conserved but with numerous secondary losses. Retromer was first identified in yeast and is ubiquitously conserved (Seaman et al, 1997;Seaman et al, 1998;Koumandou et al, 2011). The WASH complex, although widely conserved and likely to be ancient in origin (Derivery and Gautreau, 2010), is not conserved in yeast -which is also true for RME-8.…”
Section: Rme-8 Binds the Wash Complexmentioning
confidence: 99%
“…Given that retromer is conserved across all eukaryotes, 5 it is perhaps surprising that studies of retromer in mammalian cells revealed that (unlike S. cerevisiae) the complex is not a stable heteropentamer. The cargo-selective trimer is a stable complex, as is the SNX-BAR dimer but the two subcomplexes associate only transiently.…”
Section: Evolutionary Variations Of Vps29 and Their Implications Formentioning
confidence: 99%